MicroRNA‐7b attenuates ischemia/reperfusion‐induced H9C2 cardiomyocyte apoptosis via the hypoxia inducible factor‐1/p‐p38 pathway. Issue 6 (11th December 2018) - Sheng, Zulong; Lu, Wenbin; Zuo, Zhi; Wang, Dong; Zuo, Pengfei; YAO, Yuyu; Ma, Genshan
Abstract: Objective: MicroRNAs (miRNAs) have been shown to play crucial roles in the occurrence, development, and treatment of many cardiovascular diseases. Coronary heart disease (CAD)‐related miRNAs are still a growing research area. miR‐7b was reported to be downregulated in acute myocardial infarction (AMI) myocardium tissues. However, it remains largely unknown whether miR‐7b is involved in the pathogenesis and progression of the AMI ischemia/reperfusion (I/R) injury. Methods: Male C57BL/6 J mice and H9C2 cells were used as models in this study. Masson staining, real‐time polymerase chain reaction, Western blot analysis, and terminal deoxynucleotidyl transferase‐mediated dUTP nick‐end‐labeling immunofluorescence staining assays were performed to detect the related indicators in the study. SPSS 17.0 software was used to calculate the experimental data. Results: The results showed that miR‐7b expression is downregulated after I/R in mice, and miR‐7b could inhibit apoptosis in I/R‐induced H9C2 cells via upregulating hypoxia‐inducible factor 1a (HIF1a). The inhibitory effect of miR‐7b on I/R‐induced apoptosis in H9C2 cells was blocked by HIF1a silencing. In addition, our data suggested that the p‐P38 pathway may be involved in the role of miR‐7 in I/R‐induced H9C2 cell apoptosis. Conclusion: We confirmed that the overexpression of miR‐7b inhibits I/R‐induced apoptosis in H9C2 cells by targeting the HIF1a/p‐P38 pathway. Our findings not only demonstrate the potential role of miR‐7b in attenuating I/R‐induced apoptosis but also provide a new insight into the better prevention of the I/R injury by mediating HIF‐1 and p‐P38. Abstract : We confirmed that the overexpression of miR‐7b inhibits ischemia/reperfusion (I/R)‐induced apoptosis in H9C2 cells by targeting the hypoxia‐inducible factor 1a (HIF1a)/p‐P38 pathway. Our findings not only demonstrate the potential role of miR‐7b in attenuating I/R‐induced apoptosis but also provide a new insight into better prevention of the I/R injury by mediating HIF1a and p‐P38.